Health and safety: genetic relatedness of environmental exposure of lestospiral pre- and post flood: towards strategic prevention of leptospirosis - Awang @ Ismail, Nabilah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Leptospirosis is an important worldwide zoonotic disease caused by Leptospira spp. The presence of pathogenic Leptospira in the environment poses threats to human health. The aim of this study was to isolate and identify Leptospira spp. irom selected environment in flood affected areas. Method: Soil and water samples were collected about four to five months post massive flood in 2014 from selected sites in Kelantan. All samples were filtered and cultured according to previously described protocols. Molecular identification of the isolates was performed by partial sequences of 16S rRNA. Findings: A total of 90 samples comprised of 45 soil and 45 water samples were collected. Based on dark field microscopic observations, 42.2% (38/90) cultures were positive for leptospires with characteristic morphology and motility. The most predominant isolates were pathogenic Leptospira including Leptospira kmetyi, Leptospira interrogans and Leptospira kirschneri which were detected in 26.3% (I 0/38), 5.3% (2/38) and 2.6% (1/38) of the isolates respectively. Leptospira species were not able to be genetically differentiated between pre- and post-flood because single locus I 6S rRNA gene sequences has not allowed for intra species differentiation. Conclusion: This study demonstrates the predominance of clinically significant pathogenic Leptospira in the environments which could pose health risks to the community.